The Prospects of Accounting and Economic Systems in the Era of Global Knowledge Economy - Abiodun, Babalola Yisau (The Economics and Finance Letters, 2014)
This article is devoted to the study based on secondary data of journal articles and websites. There is a growing interest in research on the treatment of intangible assets in the knowledge assets [intangible assets or intellectual capital (IC)] in this digital era, or a knowledge-based economy. Various observers describe today’s global economy as one of the stages of the transition to a "knowledge economy" or "information society". But the rules and practices that determined success in the industrial economy of the 19th and 20th centuries to be changed in an environment where resources such as know-how are more critical than other economic resources. The paper highlights recent developments and thinking and provides guidance for the development of appropriate organizational strategies for success in the new millennium. It summarizes the main results of the research analyzes trends in accounting in the era of global knowledge economy.